Development of an alternative diagnostic tool for rupture risk assessment of abdominal aortic aneurysms using finite element simulation - Danao, Louis Angelo M.; Publico, Andre S.
Abdominal aortic aneurysm (AAA) rupture is the 12th leading cause of death in the United States with a rank comparable to HIV/AIDS with deaths exceeding 12,000 a year. These deaths are preventable with early detection and elective repair. The current criterion for elective repair is an aneurysm with maximum diameter of 5.5 cm. But almost 25 percent of ruptures are less than or equal to 5 cm making the criterion an unreliable predictor of rupture. From a biomechanical perspective, the best indicator of rupture is a wall stress when the mechanical stress induced exceeds the tensile strength of the tissue. One clinical case of AAA was the subject of this study. A published hyperelastic strain energy function was used as a means of reconstructing the 3D geometry of the AAA. Using finite element method, the stress distribution on the aortic wall under systolic pressure was determined and studied. Wall stress was complexly distributed on the surface of the AAA, with distinct regions of high and low stress. Peak wall stress was found to be 0.55 MPa, located at the anterior portion of the AAA. A series of simulations were done to compute for the maximum wall stress in the AAA at increasing internal pressure and varying wall thickness. A map with von Mises stress (0.65 MPa) failure line indicating the failure zone plotted on pressure versus thickness charts is developed from the recorded maximum stresses. This is the proposed alternative tool to the single critical diameter criterion. This plot will be specific to a family of AAAs with maximum diameters falling within a particular range.
Keywords: Abdominal aortic aneurysm; Finite element; Alternative diagnostic tool